EFFECTIVE INVESTMENT ACTIVITY OF AGRICULTURAL ENTERPRISES AS INSTRUMENT OF PROVIDING FOOD SECURITY OF THE COUNTRY - Samodelkin, Alexander Gennadevich; Dabakhova, Elena Vladimirovna; Bezayev, Ivan Ivanovich; Romanov, Alexander Alekseevich (V mire naučnych otkrytij, 2016)
There is a problem of development of import substitution and strengthening of food security which solution is impossible without modern and innovative means of agriculture. In this regard the investment activity necessary for ensuring reproduction processes has the main significance. The question of instruments promoting high efficiency of investment processes of agricultural enterprises is still not solved. The aim of the research is development of theoretical issues, methodical and practical recommendations about increasing the efficiency of investment activity of agricultural enterprises. Conducting the research the concept “efficiency of investment activity of agricultural enterprises” is specified and the technique of its assessment is investigated. This approbation on various levels of national economy (for the Nizhny Novgorod Region, the Volga Federal District of Russian Federation) has shown that further activization of investment processes on the basis of improvement of state mechanism of investment regulation is necessary. However, enhancement of investment activity management at the enterprises is also required. By means of the developed methodical approach the optimum level of investment security which achievement by rational distribution of state support measures will, finally, promote growth of a gross agricultural product. Practical recommendations about establishment of regulatiпg principles of investment activity directed to its increase are offered.